STUDI LITERATUR STRATEGI PEMASARAN STRAWBERRY DI PASAR TRADISIONAL DAN PASAR DIGITAL - Anggita Ken Muktiari; Intan Pijar Azzahra; Shalu Hedianti Azhara; Wien Kuntari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study is to find out the marketing strategies of strawberry in traditional markets and digital markets. Data retrieval methods use descriptive methods, literature analysis and libraries. The results of this literature discuss strawberry marketing strategies in traditional markets and digital markets. The market potential of horticultural commodities, such as strawberry, is huge in both domestic and international markets. Exploring the potential of the horticultural market, focusing on strawberry production in Indonesia, and analyzing the differences in marketing strategies between traditional markets and digital markets. STP strategies in understanding consumer preferences and positioning products can be carried out effectively. The results of this analysis also note a significant promotional role in influencing the purchase of strawberry seeds, especially in the digital market where attractive promotional strategies can increase consumer involvement and encourage sales. Strawberry production in Indonesia has increased significantly from 2021 to 2022. Effective marketing strategies are needed to increase the diversification of agricultural products and market share. The results of this literature show the difference between traditional markets and digital markets in strawberry marketing, as well as their respective advantages and disadvantages. By understanding market potential, adaptive marketing strategies, and the advantages and weaknesses of traditional markets and digital markets, strawberry producers can optimize their product marketing to achieve success in the digital era. Thus, an in-depth understanding of the market and the proper implementation of marketing strategies can increase the competitiveness of horticultural products in the domestic and international markets.